More bits - more bucks? Measuring the impact of broadband internet on firm performance - Irene Bertschek; Daniel Cerquera; Gordon J. Klein (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The paper provides empirical evidence for the causal impact of broadband Internet on the economic performance of German firms. Performance is measured in terms of labour productivity and realised process and product innovations. The analysis refers to the early phase of DSL expansion in Germany from 2001 to 2003, when roughly 60 percent of the German firms already used broadband Internet. Identification relies on instrumental variable estimation taking advantage of information on the availability of DSL broadband at the postal code level. The results show that broadband Internet has no impact on firms' labour productivity whereas it exhibits a positive and significant impact on their innovation activity.
urn:nbn:de:bsz:180-madoc-31834
Keywords: D22; L23; O31; 330; labour productivity; innovation; broadband Internet